Safety and Immunogenicity of a 20-valent Pneumococcal Conjugate Vaccine in Healthy Infants in the United States. Issue 10 (October 2021) - Senders, Shelly; Klein, Nicola P.; Lamberth, Erik; Thompson, Allison; Drozd, Jelena; Trammel, James; Peng, Yahong; Giardina, Peter C.; Jansen, Kathrin U.; Gruber, William C.; Scott, Daniel A.; Watson, Wendy
Abstract : Background: The development and widespread use of pneumococcal conjugate vaccines (PCVs) substantially reduced the global burden of pneumococcal disease. Expanding the serotypes covered by PCVs may further reduce disease burden. A 20-valent PCV (PCV20) has been developed to add coverage for 7 additional serotypes (8, 10A, 11A, 12F, 15B, 22F and 33F) to those in the existing 13-valent PCV (PCV13). This phase 2 study evaluated the safety, tolerability and immunogenicity of PCV20 in healthy US infants. Methods: In this randomized, active-controlled, double-blind study, 460 infants were randomized 1:1 to receive a 4-dose series of either PCV20 or PCV13 at 2, 4, 6 and 12 months of age. Solicited local reactions and systemic events, adverse events (AEs) and serious AEs were recorded. Immunogenicity was assessed by measuring serotype-specific IgG concentrations and opsonophagocytic activity titers at 1 month after Dose 3, before Dose 4 and 1 month after Dose 4. Results: Of 460 infants, 82.8% completed the 1-month visit after Dose 4. Local reactions and systemic events were mostly mild to moderate in severity and similar between the PCV20 and PCV13 groups. Treatment-related AEs were uncommon, with no related serious AEs or deaths reported. IgG and opsonophagocytic activity responses elicited by PCV20 were robust and demonstrated a booster response after Dose 4. Conclusions: Administration of PCV20 in US infants was well tolerated, with a safety profile similar to PCV13, and induced robust serotype-specific immune responses. These findings support continued development of PCV20 in the pediatric population. Abstract : Supplemental Digital Content is available in the text.